Biology of Vampyressa pusilla (Wagner) in Rio de Janeiro State, southeastern Brazil (Mammalia, Chiroptera, Phyllostomidae) - CEL Esbérard; HG Bergallo (Brazilian Journal of Biology)
Vampyressa pusilla is widespread in Rio de Janeiro State, southeastern Brazil. It occurs in forested areas, and is absent from urban and open habitats. This species occurs mainly in altitudes up to 1,300 m a.s.l. Vampyressa pusilla was captured during the whole night, from 18 minutes before sunset to 759 minutes after sunset. Captures peaked in the first two hours of the night. Reproductive activity was seasonal, pregnant females were observed in January, February, April, August, October, November and December and lactating females from November to January and in March.